STRUKTUR KOMUNITAS ZOOPLANKTON PADA PERAIRAN MANGROVE LAGUNA SEGARA ANAKAN CILACAP - Nur Kholifah; Eti Wahyuningsih; Dewi Kresnasari (UNU Purwokerto, 2022)
This study aims to determine the diversity of zooplankton and its connection to the quality of the mangrove waters of Segara Anakan Lagoon, Cilacap. This research was conducted from July to September 2021. The data was collected using a survey method with purposive random sampling, where the research stations were selected based on certain criteria and zooplankton samples were collected from 3 observation stations. Sampling was carried out at low tide. Zooplankton was collected using plankton net. The results showed that the types and diversity of zooplankton found in the mangrove waters of Laguna Segara Anakan Cilacap consisted of four phyla which were annelids, arthropods, protozoa, and rotifers. Only one genus found from the phylum annelids, namely polychaeta. There were six arthropods genera consisting of daphnia, microstela, nauplius, euterfina, diaphanossoma, and oithona. The phylum Protozoa consists of one genus, astramoeba, while the phylum rotifera consists of two genera, Branchionus and Notholca. The abundance of zooplankton at Stations 1, 2, and 3 were 1.61 ind/l, 1.84 ind/l, and 1.41 ind/l, respectively. Zooplankton diversity is influenced by aquatic environmental conditions such as air temperature, water temperature, dissolved oxygen, water pH, salinity, and TSS.